Percepções sobre o mestrado profissional e seu impacto no desempenho dos egressos - Oliveira, Lívia Dias de (2008)
In Brazil, CAPES has the responsibility of evaluation and accreditation of graduate strict programs. The CAPES work also drives the strategies adopted by the evaluated programs. The Professionals Masters Programs (PMP) are the newer modality of graduate program in Brazil and presents major difficulties for their evaluation. This work presents a questionnaire based model to evaluate perceptions about the impact of PMP in its alumni s skills. This model was applied in a specific situation, collecting and analyzing perceptions from students, company, teachers and coordinators of PMP that are in the Engineering III group (CAPES classification). This work also presents the literature review, which strongly contributes to the questionnaire building and the criteria definition. Among other relevant results, the present application highlighted the criteria with the highest performance and importance levels. The company had a more optimistic view, and teachers were more demanding about the impact of the Professional Masters in its alumni s performance.